GAYA KOMUNIKASI AHOK BERDASARKAN PERSPEKTIF KOMUNIKASI LINTAS BUDAYA - Aprilyanti Pratiwi (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2019)
2019 is the year of Ahok's return after serving a prison sentence of 2 years. It is still embedded in people's memories of how the character of Ahok as a leader is very different from the character of leaders in Indonesia. The purpose of this study is to analyze Ahok's communication style while serving as the Governor of DKI Jakarta in terms of the context of cross-cultural communication. The method used in this study is qualitative by analyzing online news that displays Ahok's communication style. In addition, this study also uses literature studies in the form of previous research literature that examines Ahok's communication style. The results showed that based on cross-cultural perspectives, Ahok as an official and or political elite used Low Context Culture (LCC) communication style. Ahok displays a communication style that is outspoken or to the point. He paid little attention to the value system. If he considers that other people wrong, then he does not hesitate to say it without caring what he expressed is contrary to the values adopted by the people of Indonesia. However, there are several Ahok communication styles that do not conform to the characteristics of the LCC, namely when speaking Ahok tends to use non-formal language with high voice intonation.